Pergeseran Representasi Perempuan dan Laki-Laki Pada Video Musik You Belong With Me dan The Man dari Taylor Swift - Putri, Dyas Adinda Santana (Tuturlogi: Journal of Southeast Asian Communication, 2021)
This research focuses on the representation of women and men in the music videos "You Belong With Me" and "The Man" by Taylor Swift which are studied from the perspective of hegemonic masculinity, hegemonic femininity, post-feminism and celebrity feminism. This study uses the theory of hegemonic masculinity from Connell and hegemonic femininity from Collins which explains forms of gender practices that answer problems related to patriarchal legitimacy, and guarantee the dominant position of men and the subordination of women. This study also uses the post-feminist sensibility of Rosalind Gill, which shows the pattern of post-feminism discourse. The method used in this study is intercoder reliability in qualitative research, which is used to analyze the discourse of women and men represented in both music videos and their changes, which are seen from the perspective of hegemonic masculinity, hegemonic femininity, and post-feminism. The results of the analysis show that there is a shift in the representation of women and men in the music videos for You Belong With Me and The Man by Taylor Swift, which makes women from inferior figures to superior ones while men from 'angels' figures to 'devils'. The superior woman in The Man's music video is shaped through a post-feminist sensibility culture with individualistic notions of choice and success. The element of choice is shown by consciously choosing to appear freely without wanting to be judged. Elements of success can be seen through Taylor Swift who has a career and is wealthy so she doesn't have financial anxiety to go wild, and her efforts to achieve this success are shown by her independence and self-determination.